2007
DOI: 10.2174/092986607781483813
|View full text |Cite
|
Sign up to set email alerts
|

Scanning the Genome of Mycobacterium tuberculosis to Identify Potential Lectins

Abstract: Lectins are carbohydrate binding proteins with important roles in many biological processes such as adhesion. Here we have identified 11 potential lectins from Mycobacterium tuberculosis H37Rv genome, using a comprehensive bioinformatics analysis, which will provide helpful clues in molecular mapping of pathogenesis and perhaps also serve as potential drug targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…These results are consistent with the varying carbohydrate-binding characteristics observed between different mycobacterial species, as described above [12,74]. While three potential glycan-binding proteins were identified in the Mtb (H37Rv) genome in this study (Table 3) [77], Singh et al, using a different suite of bioinformatic tools, identified eleven, of which nine were annotated as potential lectins [78]. However, most of the proteins encoded by these genes have yet to be biochemically characterized, precluding further functional predictions.…”
Section: Reviewsupporting
confidence: 90%
See 4 more Smart Citations
“…These results are consistent with the varying carbohydrate-binding characteristics observed between different mycobacterial species, as described above [12,74]. While three potential glycan-binding proteins were identified in the Mtb (H37Rv) genome in this study (Table 3) [77], Singh et al, using a different suite of bioinformatic tools, identified eleven, of which nine were annotated as potential lectins [78]. However, most of the proteins encoded by these genes have yet to be biochemically characterized, precluding further functional predictions.…”
Section: Reviewsupporting
confidence: 90%
“…Exceptions are the secreted 13 kDa large lectin from Mtb , sMTL-13 [7980], and the heparin-binding hemagglutinin (HBHA) [8185], which have been previously studied in detail (see below). We subsequently discuss the association of the nine putative Mtb lectins identified by Singh et al and Abhinav et al with established lectin families [7778], such as agglutinin-like sequences (ALS), mannose-sensitive hemagglutinin (MSHA), C-type lectins, and R-type lectins. Furthermore, the filamentous hemagglutinin (FHA) and the heparin-binding hemagglutinin (HBHA) as glycosaminoglycan-binding protein families are also discussed (Table 3, Fig.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations